The Synthetic Biology Open Language (SBOL) provides a community standard for communicating designs in synthetic biology - Galdzicki, Michal; Clancy, Kevin P; Oberortner, Ernst; Pocock, Matthew; Quinn, Jacqueline Y; Rodriguez, Cesar A; Roehner, Nicholas; Wilson, Mandy L; Adam, Laura; Anderson, J Christopher; Bartley, Bryan A; Beal, Jacob; et al. (Nature biotechnology, 2014)
The synthetic biology research community describes a standard language for exchanging designs of biological 'parts'. The re-use of previously validated designs is critical to the evolution of synthetic biology from a research discipline to an engineering practice. Here we describe the Synthetic Biology Open Language (SBOL), a proposed data standard for exchanging designs within the synthetic biology community. SBOL represents synthetic biology designs in a community-driven, formalized format for exchange between software tools, research groups and commercial service providers. The SBOL Developers Group has implemented SBOL as an XML/RDF serialization and provides software libraries and specification documentation to help developers implement SBOL in their own software. We describe early successes, including a demonstration of the utility of SBOL for information exchange between several different software tools and repositories from both academic and industrial partners. As a community-driven standard, SBOL will be updated as synthetic biology evolves to provide specific capabilities for different aspects of the synthetic biology workflow.